DIAGNOSIS MOLEKUL DAN APLIKASI DALAM PENGOBATAN HEPATITIS B & C - Aryati Aryati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
In the whole world, up to now hepatitis B and C virus are still the main causes of chronic hepatitis, cirrhosis until hepatocellularcarcinoma. Most diagnosis is based on a serological examination such as the determination of antigen and antibody, for exampleHbsAg, HbeAg and anti HCV. Recently, for hepatitis C examination, HCV core antigen is used for the detection of HCV infection duringthe window period, chronic C hepatitis and for treatment monitoring. At present, serological assays are not sufficient to confirm thediagnosis of hepatitis B and C due to mutations of false negative HbsAg or HbeAg results. Occult hepatitis B can occur with a negativeresult of HbsAg, which cause difficulties in confirming the diagnosis and treatment as well. The success of treatment can be influencedof both hepatitis B and hepatitis C that have genotypes. By using molecular examination, such as determination of HBV-DNA and HCVRNA,it is expected that the problem of serological determination can be overcome. Molecular examination is not only useful for just thediagnosis confirmation, such as for active phase and replicative determination. This sequence is also very useful as a data base prior tothe treatment of hepatitis B and hepatitis C as well as for their following success result.